Blood-CNS barrier dysfunction in amyotrophic lateral sclerosis: Proposed mechanisms and clinical implications. Issue 5 (May 2023) - Steinruecke, Moritz; Lonergan, Rebecca Murphy; Selvaraj, Bhuvaneish T; Chandran, Siddharthan; Diaz-Castro, Blanca; Stavrou, Maria
There is strong evidence for blood-brain and blood-spinal cord barrier dysfunction at the early stages of many neurodegenerative diseases, including amyotrophic lateral sclerosis (ALS). Since impairment of the blood-central nervous system barrier (BCNSB) occurs during the pre-symptomatic stages of ALS, the mechanisms underlying this pathology are likely also involved in the ALS disease process. In this review, we explore how drivers of ALS disease, particularly mitochondrial dysfunction, astrocyte pathology and neuroinflammation, may contribute to BCNSB impairment. Mitochondria are highly abundant in BCNSB tissue and mitochondrial dysfunction in ALS contributes to motor neuron death. Likewise, astrocytes adopt key physical, transport and metabolic functions at the barrier, many of which are impaired in ALS. Astrocytes also show raised expression of inflammatory markers in ALS and ablating ALS-causing transgenes in astrocytes slows disease progression. In addition, key drivers of neuroinflammation, including TAR DNA-binding protein 43 (TDP-43) pathology, matrix metalloproteinase activation and systemic inflammation, affect BCNSB integrity in ALS. Finally, we discuss the translational implications of BCNSB dysfunction in ALS, including the development of biomarkers for disease onset and progression, approaches aimed at restoring BCNSB integrity and in vitro modelling of the neurogliovascular system.